2015
DOI: 10.1002/soej.12118
|View full text |Cite
|
Sign up to set email alerts
|

Price-Match Announcements in a Consumer Search Duopoly

Abstract: Using a model of sequential search, we show that announcements to price-match raise prices by altering consumer search behavior. First, price-matching diminishes firms incentives to lower prices to attract consumers who have no search costs. Second, for consumers with positive search costs, price-matching lowers the marginal benefit of search, inducing them to accept higher prices. Finally, price-matching can lead to asymmetric equilibria where one firm runs fewer sales and both firms tend to offer smaller dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The idea is that, when consumers are heterogeneous, PMG can be used to price discriminate one consumer type over the others. Janssen and Parakhonyak (2013) and Yankelevich and Vaughan (2016) both investigate the price discrimination role of PMG within the endogenous search framework. In Janssen and Parakhonyak (2013), some consumers with high search cost do not search in equilibrium but are able to passively receive a price quote after purchase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The idea is that, when consumers are heterogeneous, PMG can be used to price discriminate one consumer type over the others. Janssen and Parakhonyak (2013) and Yankelevich and Vaughan (2016) both investigate the price discrimination role of PMG within the endogenous search framework. In Janssen and Parakhonyak (2013), some consumers with high search cost do not search in equilibrium but are able to passively receive a price quote after purchase.…”
mentioning
confidence: 99%
“…Consequently, PMG increases consumers' option value of purchase and knowing this, all retailers charge a higher price. Yankelevich and Vaughan (2016) assume that some shoppers patronize PMG retailers only and will invoke PMG if a lower price exists. As a result, PMG increases retail prices.…”
mentioning
confidence: 99%
“…Besides [8], there are a growing stream of literature choose price matching. Yankelevich and Vaughan [31] found that announcements to price-match raise prices by altering heterogeneous consumer search behavior by using a model of sequential search. Price increases grow in the proportion of consumers who invoke price-matching guarantees and in the level of equilibrium asymmetry.…”
Section: Literature On the Impact Of Dynamic Pricing And Price Matmentioning
confidence: 99%
“…Whereas Janssen and Parakhonyak (2013) assume that no consumer knows which firms offer PMGs, Jiang, Kumar, and Ratchford (2016) and Yankelevich and Vaughan (2016) assume the opposite: all consumers know which firms provide a PMG. In either case, PMGs cannot act as a signal of low prices.…”
Section: Related Literaturementioning
confidence: 99%